Protocolizing the Workup for Idiopathic Normal Pressure Hydrocephalus Improves Outcomes. Issue 4 (August 2021) - Acosta, Lealani Mae Y.; Stubblefield, Kassandra; Conwell, Trisha; Espaillat, Kiersten; Koons, Heather; Konrad, Peter; Fang, John; Kirshner, Howard; Davis, Thomas
Abstract : Background: The workup for idiopathic normal pressure hydrocephalus (INPH) can be difficult to coordinate, and determining appropriate patients for ventriculoperitoneal shunting can be challenging. Therefore, we hypothesized that implementing a formalized protocol can improve patient selection for a shunt. In conjunction with neurology and neurosurgery, we instituted a standardized means of assessing patients whose presentation is concerning for INPH and compared their workup with similar patients seen without the Protocol (i.e., preprotocol [PP]) regarding baseline characteristics, assessment, and outcomes. Methods: Twenty-six PP patients were compared with 40 Protocol patients on measures, including baseline deficits, workup, neurosurgical evaluation, and response to shunt. Results: Average age was similar between groups, and the percentage of patients who had a decline in gait, cognition, and/or incontinence was not statistically different ( p > 0.05). Significantly more Protocol patients underwent high-volume lumbar puncture (HVLP; 97.5%; PP, 61.5%; p < 0.001) and received formalized gait assessment with the Gait Scale (90%; PP, 0%, p < 0.001) and standardized cognitive testing (95%; PP, 38.5%; p < 0.001). Significantly more Protocol patients had no improvement after HVLP (33.3%; PP, 6.25%; p < 0.045); subsequently, fewer got shunted (57.5%; PP, 84.6%; p < 0.030). More Protocol patients who were shunted reported gait improvement (100%; PP, 72.7%; p = 0.009), although there was no difference in cognition (59.2%; PP, 82.6%; p = 0.108) or incontinence (18.2%; PP, 39.1%; p = 0.189). Conclusions: Implementing an INPH Protocol leads to standardized and more extensive assessment and better patient selection for and subsequent outcomes from shunting, specifically regarding gait.